2006
DOI: 10.1002/chp.59
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physicians' self-assessment and quality improvement: The ABIM diabetes practice improvement module

Abstract: Self-assessment using the ABIM diabetes PIM as part of recertification provides valuable practice information and can lead to meaningful behavioral change by physicians. Collaboration with an educator in quality improvement appears to facilitate the effects of the practice improvement module. Future work should investigate the effect on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 15 publications
0
52
0
Order By: Relevance
“…Second, there was no audit process to ensure that instructions for sampling and data extraction were followed. However, prior work confirmed the accuracy of physician-reported data in a quality improvement framework, 27 and physicians had no reason to provide false results as there were no consequences for low or …”
Section: Discussionmentioning
confidence: 95%
“…Second, there was no audit process to ensure that instructions for sampling and data extraction were followed. However, prior work confirmed the accuracy of physician-reported data in a quality improvement framework, 27 and physicians had no reason to provide false results as there were no consequences for low or …”
Section: Discussionmentioning
confidence: 95%
“…Prior work showed that practices can reliably and accurately abstract and report data from their medical records. 9 A potential limitation of our study is that physicians may have selectively chosen patients in an effort to boost their quality measures. Previous research, however, found that patient selection by physicians engaged in maintenance of certification projects was unbiased, as the primary goals were educational.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the sampling strategy and accuracy of chart data were not audited (there was no penalty for poor performance on the PIM); however previous work has confirmed the accuracy of physicianreported data in the Diabetes PIM. 29 It is possible that some physicians may not have adhered to the sampling instructions and their performance on individual measures might be inflated.…”
Section: Discussionmentioning
confidence: 99%